Web-based application of the internship management system / Fazeera Syuhada Abdullah ... [et al.] - Abdullah, Fazeera Syuhada; Abu Seman, Azmi; Ibrahim, Norfiza; Majid, Noor Aishatun; Abdul Wahab, Nor Mazlina; Mustafa, Mohd Syamaizar; Mohd Sani, Noor Faezah (UiTM Cawangan Perlis, 2017)
Placement of students in the industry or organization related to their study field is compulsory in order to fulfill the requirement of Ministry of Higher Education policy. It became one of the courses that must be fulfilled by students in order to finish their study at university or other institutions. Increment on the number of students in universities caused the management of internship program become uncontrolled. At UiTM Perlis, students who have been using the manual system in conducting internship have caused many problems. The main problem exists in UiTM Perlis is the manual management in internship program which involves a lot of paper, time-consuming and poor management between academician and industry as well as students. Thus, an internship management system using case-based in web environment is developed to solve the problem that occurred among students, coordinator and employer. The system will help in reducing the workload to the three users mentioned previously. Based on the system, the requirements from the industry will be matched with the qualification from the students. Therefore, the placement for the students will be easily generated by the system. Two methods of testing were conducted namely heuristic evaluation and user acceptance test. The results proved that the systematic online industrial training application system achieved very good level of performance in terms of user interface satisfaction, usefulness and ease of use and its usability by users.